Lifestyle, emotional self dis-closure, and psychological well-being of Aglipayan seminarians by Mary Georgel Lobaton Garrucha. - Garrucha, Mary Georgel Lobaton
This is a descriptive stuy aimed to determine the lifestyle, emotional self-disclosure and psychological well-being of seminarians., Rresults from convenient sampling of 15 respondents aging 21 to 55 revealed that the life of the seminarians is particularly based on the daily time rule defined by the seminary in accordance to the goals, vision, and mission of the seminary as a preparation to their future as priest. Their daily time schedule allows them to have some free time for leisure activities. The seminarians are also able to undertake the different community-based activities as part of the curriculum of the seminary. Majority of the seminarians disclose their emotions to others whenever they feel happy and contented, and they least disclose themselves whenever they feel jealous or envious. The seminarians disclosed themselves mostly to their fellow seminarians, or to the bishop of their parish. Seminarians have high level of psychological well-being. Almost all were able to get the highest score on purpose in life dimension.